1983
DOI: 10.1002/jcp.1041140312
|View full text |Cite
|
Sign up to set email alerts
|

Bovine endothelial cells transformed in vitro by benzo(a)pyrene

Abstract: A cloned strain of bovine vascular endothelial cells with a finite in vitro lifespan was treated with benzo(a)pyrene (BP) after approximately 75% of its lifespan was completed. Untreated cultures of this strain senesced upon serial subcultivation and contained large, nondividing cells. In three out of seven trials, BP treatment produced transformed lines with altered phenotypic characteristics. The transformed cells appeared in the cultures concomitant with the senescence of the parent cells. All transformed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…Then, radioactivity bound to high a nity FGFRs was measured FGF2 and FGF4 are able to exert a signi®cant mitogenic response also in this endothelial cell type (data not shown). Similar results were obtained when conditioned media and recombinant proteins were tested in the fetal bovine aortic endothelial GM7373 cell line (Grinspan et al, 1983) (data not shown).…”
Section: Fgf4 Overexpression In Mae Cells: Effects In Vivosupporting
confidence: 83%
“…Then, radioactivity bound to high a nity FGFRs was measured FGF2 and FGF4 are able to exert a signi®cant mitogenic response also in this endothelial cell type (data not shown). Similar results were obtained when conditioned media and recombinant proteins were tested in the fetal bovine aortic endothelial GM7373 cell line (Grinspan et al, 1983) (data not shown).…”
Section: Fgf4 Overexpression In Mae Cells: Effects In Vivosupporting
confidence: 83%
“…GM 7373 cells were used because basal nitric oxide metabolism is pronounced compared with EA.hy 926 cells and thus more suitable for nitrite analysis. In short, confluent GM 7373 cells (45) were cultured in T 75 flasks in low sodium (135 mM sodium, in the absence or presence of 0.45 nM aldosterone) and high sodium (150 mM, in the absence or presence of aldosterone) medium. Mannitol (30 mM) was added to the low sodium medium for maintaining isoosmolality.…”
Section: Methodsmentioning
confidence: 99%
“…HL3T1 cells were maintained in DMEM (Gibco, Grand Island, NY) supplemented with 10% FCS, 100 U/ml penicillin and 100 U/ml streptomycin (Broder et al, 1997). Transformed fetal bovine aortic endothelial GM7373 cells (Grinspan et al, 1983) were grown in DMEM supplemented with 10% FCS.…”
Section: Cell Culturesmentioning
confidence: 99%